Sosiologi Lembaga Pendidikan Madrasah Aliyah: Studi tentang Akuntabilitas Sekolah dan Dampaknya terhadap Praktik Pengajaran Guru di Era Kurikulum Merdeka - Saif ‘Abdul Fatah; Muh. Hanif (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The Merdeka Curriculum is currently having an impact on the world of education, particularly in terms of accountability regarding teachers’ performance in carrying out their duties as educators. Unlike previous curricula, under the Merdeka Curriculum teachers are required to fulfil a dual role; in addition to being educators, they also bear responsibility for administrative tasks. This issue highlights the fact that teachers play a crucial role in addressing the challenges presented by the Merdeka Curriculum. This study employs a qualitative approach using a case study design to provide an in-depth understanding of school accountability regarding teachers’ teaching practices. The data collection methods used are observation, interviews, and documentation, with a focus on MAN 1 Banyumas. The results of this study indicate that school accountability in the era of the independent curriculum serves as a catalyst for teachers to be more creative. Administrative demands do not act as a barrier for teachers, thereby hindering their performance in classroom teaching. Furthermore, at the Madrasah Aliyah itself, a Teachers’ Working Group (MGMP) has been established, serving as a forum for teachers to collaboratively seek solutions to existing problems.